2014
DOI: 10.1371/journal.pone.0107860
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Genomic Analysis of Korean Porcine Sapelovirus Strains

Abstract: Porcine sapelovirus (PSV), a species of the genus Sapelovirus within the family Picornaviridae, is associated with diarrhea, pneumonia, severe neurological disorders, and reproductive failure in pigs. However, the structural features of the complete PSV genome remain largely unknown. To analyze the structural features of PSV genomes, the full-length nucleotide sequences of three Korean PSV strains were determined and analyzed using bioinformatic techniques in comparison with other known PSV strains. The Korean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 49 publications
4
48
0
Order By: Relevance
“…Contrary to our data, a recent study has reported that neuroinvasive English SV-A strain replication in the spinal cord could lead to severe adaptive immune responses (non-suppurative polioencephalomyelitis) without causing lesions in other tissues (Schock et al , 2014). This English SV-A strain (G5) is phylogenetically closer to the English V13 strain than to other SV-A strains circulating recently in Korea and China (Schock et al , 2014; Son et al , 2014a). The molecular basis involved in the differences in virulence and tropism among SV-A strains remains unknown.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Contrary to our data, a recent study has reported that neuroinvasive English SV-A strain replication in the spinal cord could lead to severe adaptive immune responses (non-suppurative polioencephalomyelitis) without causing lesions in other tissues (Schock et al , 2014). This English SV-A strain (G5) is phylogenetically closer to the English V13 strain than to other SV-A strains circulating recently in Korea and China (Schock et al , 2014; Son et al , 2014a). The molecular basis involved in the differences in virulence and tropism among SV-A strains remains unknown.…”
Section: Discussionmentioning
confidence: 76%
“…Viruses in this family can cause a wide range of diseases, including intestinal, respiratory, neurological, cardiac, hepatic, mucocutaneous and systemic diseases of various severities in both humans and animals (Racaniello, 2013). Since porcine enterovirus 8 (PEV-8), simian type 2 picornavirus and duck picornavirus TW90A have a unique genomic organization different from other picornavirus genera (Son et al , 2014a), the genus Sapelovirus is a newly assigned member of the Picornaviridae family (Adams et al , 2015). The Sapelovirus genus consists of three species: Sapelovirus A (SV-A) formerly known as porcine sapelovirus, Sapelovirus B formerly named as simian sapelovirus and Avian sapelovirus formerly known as duck picornavirus TW90A (Adams et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These structures are similar in the different genera of Picornaviridae although the location of these elements varies and overall their nucleotide sequences are highly divergent (Figs. 4A, 4B): cre s of PV and CVB3 ( Enterovirus ) in 2C ATPase (55, 164); cre s of HRV14, HRV3 and HRV76 ( Enterovirus ) in VP1 (89, 90); cre s of HRV2, HRV1a, HRV16 ( Enterovirus ) (52, 89); cre of species C Rhinovirus ( Enterovirus ) in VP2 (30); cre of TMEV and Mengovirus ( Cardiovirus) in VP2 (83); cre of HAV ( Hepatovirus) in 3D pol (178); cre of HPeV (Parechovirus) in VP0 (2); cre of Porcine Sapelovirus ( Sapelovirus ) in 2C ATPase (142). The only known exception is FMDV ( Aphthovirus ) whose cre is located in the 5’NTR rather than the coding sequences (88).…”
Section: Factors Involved In the Initiation Of Protein-primed Rna mentioning
confidence: 99%